Extending the Analysis of Functional Ability Trajectories to Unexplored National Contexts: The Case of Chile. (28th June 2021) - Madero-Cabib, Ignacio; Villalobos Dintrans, Pablo; Browne Salas, Jorge
Abstract: Objectives: Despite the enormous advances in the field, most evidence about functional ability trajectories in old age comes from studies conducted in developed and high-income countries. This research aims to build on these previous advances to examine functional ability trajectories in Chile. Method: Drawing on a robust, publicly available 15-year panel data set (2004–2018), and using sequence analysis, we examine functional ability trajectories types among 4 age groups (people aged 46–50, 51–55, 56–60, and 61–64 at baseline). Then, we analyze trajectories' dynamics looking at intraindividual health-declining and health-recovery transitions between functional ability statuses, within each trajectory type. Finally, we assess how multiple baseline individual characteristics predict the likelihood of following a functional ability trajectory type, using multinomial regression models. Results: Across all age groups, an important fraction (between 26% and 50%) reports stable healthy trajectories, and between 10% and 20% follow equivocal-declining trajectories (i.e., exhibiting both health-declining and health-recovery intraindividual transitions), suggesting that age might not be the main source of heterogeneity in functional ability trajectories. Overall, women, lower educated people, nonworking individuals, and people with a higher burden of chronic conditions at baseline are more prevalent among health-declining trajectory types; however, these results are not constant across the age groups analyzed. Discussion: This nationally focused study reinforces the feasibility and usefulness of an in-depth analysis of functional ability trajectories in old age. The study findings can be crucial to define different prevention strategies according to the functional ability path that an individual might follow, especially in countries like Chile that currently navigate the challenges of population aging.